Negotiation of Needs Towards Halal Talents Sustainability - Norhayati Rafida Abdul Rahim; Ismail Abdullah; Noor Azrina Yahya; Muhammad Nizam Awang; Siti Zubaidah Muhammad; Safiyyah Ahmad Sabri; Norfaizah Nadhrah Ahmad (Emerald Group Publishing, 2024)
Indexed by Scopus